2019
DOI: 10.1111/jfpp.14125
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and characterization of antioxidant potential, in vitro protein digestion and structural attributes of microwave processed multigrain pasta

Abstract: A central composite design was used to optimize flour combination consisting of sorghum flour (20%–35%), finger millet flour (10%–25%) and gluten (3%–5%) on five responses, namely cooking loss (CL), cooking time (CT), water absorption index (WAI), firmness, and overall acceptability (OA) of multigrain pasta. The optimized pasta was evaluated for physicochemical, antioxidant/anti‐nutritional, in vitro protein digestibility (IVPD), and structural attributes. Optimum level for sorghum, finger millet, and gluten w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 40 publications
6
33
0
Order By: Relevance
“…A decrease in the intensities of the peaks may due to crystallite disruption or reorientation of the double helices creating the crystalline array due to the heat treatment (during drying) that gelatinises its starch ( Dharmaraj et al., 2014 ). The A-typical arrangements of the diffraction patterns with high peaks were noticed in the processed and unprocessed flours of Agrigreen , Babala and sorghum were similar to other cereals reported by Kamble et al. (2019) , Yang et al.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A decrease in the intensities of the peaks may due to crystallite disruption or reorientation of the double helices creating the crystalline array due to the heat treatment (during drying) that gelatinises its starch ( Dharmaraj et al., 2014 ). The A-typical arrangements of the diffraction patterns with high peaks were noticed in the processed and unprocessed flours of Agrigreen , Babala and sorghum were similar to other cereals reported by Kamble et al. (2019) , Yang et al.…”
Section: Resultssupporting
confidence: 84%
“…These changes in peaks could be related to increasing in the functional, better lipophilic and hydrophilic properties and the extent of inter and intramolecular bond of the MFAF, MFBF and MFSF flour sample ( Sun et al., 2014 ). The results of Kamble et al. (2019) are in close range of peaks for the pasta produced from sorghum-finger millet with gluten.…”
Section: Resultsmentioning
confidence: 65%
“…Most of these additional ingredients has focused on manipulation of glycaemic index (GI) since clinical reports have suggested that food with low GI has been directly associated with the reduced risks of hyperlipidaemia, cardiovascular diseases, extending satiety, and improved insulin sensitivity (Chillo, Ranawana, & Henry, 2011;Dona, Pages, Gilbert, & Kuchel, 2010). Researchers have developed the pasta with various bioactive ingredients such as pasta from fish material (Desai, Brennan, & Brennan, 2019;Desai et al, 2018;Parvathy, Bindu, & Joshy, 2017), mushroom powder-based pasta (Gao, Brennan, Mason, & Brennan, 2016;Lu et al, 2018), millets pasta (Gull, Prasad, & Kumar, 2015;Jalgaonkar & Jha, 2016;Kamble et al, 2019), cereal, pseudocereal, and super grain-enriched pasta (Benhur et al, 2015;Menga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the range of quality and nutritional characteristics of noodles, auxiliary materials or additives, including starch and modified starch, may be used. For instance, addition of mushroom flour, sorghum flour or finger millet flour increased antioxidant activity and reduced glycemic index of pasta (Lu et al, 2018;Kamble et al, 2019Kamble et al, , 2020 and noodle (Rani et al, 2019). The introduction of starch also could alter the texture of noodles by increasing their hardness, elasticity or chewiness (Obadi & Xu, 2020).…”
Section: Introductionmentioning
confidence: 99%